The DART Project : making the intangible tangible - Arts & Humanities Research Council; Engineering and Physical Sciences Research Council (2010)
[Dt.:] Web-Log zu Luftbildarchäologie und archäologischen Survey-Projekten Großbritanniens mit Bildergallerien, Eventkalender und Bibliographien. - [Engl.:] The web-log informs about aerial archaeology and survey projects in Great Britain including picture galleries, informations about events and bibliographies.